Contributing Efforts of Various String Matching Methodologies in Real World Applications - Soni, Kapil Kumar (International Journal of Computer Sciences and Engineering, 2025)
String matching is a conventional problem in computer science. For a known text string ‘T’, the problem of string matching is to locate whether a pattern string ‘P’ occurs in ‘T’ or not, and if ‘P’ occurs then the position of ‘P’ in ‘T’ is reported. String matching sometimes called string searching has become an important aspect of the real world because it is being used in many applications where the string algorithm tries to find a location of one or several strings (also called Patterns) within a larger string or text (Text Data Set). A few of its essential applications are Spell Checkers, Spam Filters, Intrusion Detection System, Search Engines, Plagiarism Detection, Bioinformatics, Digital Forensics and Information Retrieval Systems, etc. The paper includes various string matching methodologies along with its historical contributory details in a variety of needful real world applications.